Agroforestry As an Ecological Approach to Support The Sustainability of Dryland Agroecosystems in Pringgabaya District, East Lombok - Yusuf, M.; Astiko, Wahyu (Jurnal Biologi Tropis, 2025)
Agroforestry plays a strategic role in maintaining the ecological function of dry lands while improving community welfare in a sustainable manner. The aims of this research are to: (1) describe the concept, benefits, principles, and constraints of agroforestry application on dry land in Pringgabaya District, East Lombok; (2) analyze relevant agroforestry models and their impacts on agroecosystem sustainability; and (3) analyze farmers' perceptions and adoption levels of agroforestry systems. The method used is a descriptive method, while data collection uses survey techniques and literature studies. The results of the study indicate that: (1) Agroforestry is a sustainable land management system that integrates trees, agricultural crops, and/or livestock in a spatial and temporal order designed to increase synergistic interactions; The benefits of agroforestry include: soil and water conservation, increased fertility, income diversification, resilience to extreme climates, and increased biodiversity; The main principles of agroforestry include: spatial-temporal integration, selection of appropriate species, closed nutrient cycles, resource conservation, and local wisdom. The main constraints of agroforestry in this area include; biophysical aspects (undulating, hilly and mountainous topography, with shallow and rocky soil, limited water availability, low rainfall (1,000-2,000 mm/year), and low soil fertility); socio-economic aspects such as limited capital, technology, knowledge, market access, and minimal policy support; (2) Models relevant to dry land in Pringgabaya District, East Lombok include: alley cropping, silvopasture, agrisilviculture, agrosilvopasture, productive yards, and windbreak agroforestry. Their impacts on sustainability include ecological aspects (soil conservation, water efficiency, and fertility), socio-economic (income, local capacity, food security), climate (microclimate and mitigation), and biodiversity. Farmers' perceptions of agroforestry are very positive, with an adoption rate reaching 81.22%.